2012
DOI: 10.4161/cc.21019
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 inhibits hepatic lipogenesis via repression of carbohydrate response element binding protein and hepatocyte nuclear factor 4α

Abstract: Following acute hepatic injury, the metabolic capacity of the liver is altered during the process of compensatory hepatocyte proliferation by undefined mechanisms. In this study, we examined the regulation of de novo lipogenesis by cyclin D1, a key mediator of hepatocyte cell cycle progression. In primary hepatocytes, cyclin D1 significantly impaired lipogenesis in response to glucose stimulation. Cyclin D1 inhibited the glucose-mediated induction of key lipogenic genes, and similar effects were seen using a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 38 publications
(70 reference statements)
6
82
1
Order By: Relevance
“…Indeed, many terminal cell systems couple cell cycle inhibition with differentiation (1), and many potent transcription factors interact with cell cycle components in ways similar to MyoD, including Ngn2, Pdx1, Smad3, Mitf, Runx2, PU.1, Hnf4α, and C/EBPβ (17)(18)(19)(20)(21)(22)(23)(24). Whereas experimental validation and extension of our findings with MyoD to other lineages remains to be Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many terminal cell systems couple cell cycle inhibition with differentiation (1), and many potent transcription factors interact with cell cycle components in ways similar to MyoD, including Ngn2, Pdx1, Smad3, Mitf, Runx2, PU.1, Hnf4α, and C/EBPβ (17)(18)(19)(20)(21)(22)(23)(24). Whereas experimental validation and extension of our findings with MyoD to other lineages remains to be Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that Cdk8/cyclin C-dependent phosphorylation of Srebp-1c blocked the lipogenic pathway by targeting Srebp-1c for ubiquitin-mediated degradation (Zhao et al, 2012). Cyclin D1 also inhibits hepatic lipogenesis but its effects were mediated through the repression of two other transcription factors involved in the expression of lipogenic genes: carbohydrate response element-binding protein (ChREBP; Mlxipl) and hepatocyte nuclear factor 4α (Hnf4α) (Hanse et al, 2012). It is tempting to speculate that cell cycle regulators limit the conversion of glucose to lipids for storage so that energy resources can be reallocated to meet the increased demands during cell proliferation.…”
Section: Cdks Cyclins and Ckis Regulating Metabolismmentioning
confidence: 99%
“…1C). Finally, we measured the levels of the cell cycle regulator CYCLIN D1, a well-established regulator of cell growth known to be up-regulated during liver regeneration (28,29). The induction of CYCLIN D1 expression was significantly decreased in SULF2-KO mice at 36 and 48 h after PH (Fig.…”
Section: Loss Of Sulf2 Delays Liver Regenerationmentioning
confidence: 99%